2014
DOI: 10.5411/wji.v4.i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Role of myeloid-derived suppressor cells in autoimmune disease

Abstract: Myeloid-derived suppressor cells (MDSCs) represent an important class of immunoregulatory cells that can be activated to suppress T cell functions. These MDSCs can inhibit T cell functions through cell surface interactions and the release of soluble mediators. MDSCs accumulate in the inflamed tissues and lymphoid organs of patients with autoimmune diseases. Much of our knowledge of MDSC function has come from studies involving cancer models, however many recent studies have helped to characterize MDSC involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 80 publications
0
52
0
1
Order By: Relevance
“…MDSCs have been shown to regulate immune responses during autoimmune conditions (181, 182). It has been suggested that MDSCs suppress T cell activity through the secretion of inducible nitric oxide synthase (iNOS) and arginase-1 (182).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDSCs have been shown to regulate immune responses during autoimmune conditions (181, 182). It has been suggested that MDSCs suppress T cell activity through the secretion of inducible nitric oxide synthase (iNOS) and arginase-1 (182).…”
Section: Introductionmentioning
confidence: 99%
“…MDSCs have been shown to regulate immune responses during autoimmune conditions (181, 182). It has been suggested that MDSCs suppress T cell activity through the secretion of inducible nitric oxide synthase (iNOS) and arginase-1 (182). GM-CSF has been shown to not only promote the development of MDSCs from bone marrow precursors (183) but also determine their suppressive capacities (184).…”
Section: Introductionmentioning
confidence: 99%
“…Their trafficking is mainly dictated by the chemokine receptor CCR2. [84, 85] They are found in mouse models of rheumatoid arthritis, diabetes and multiple sclerosis (EAE). Peripheral blood naïve monocytes (CD11b +, Ly6G − ) also display in vitro intrinsic suppressive properties by inhibiting T cell proliferation through a mechanism that requires cell-contact and partially, nitric oxide (NO) production.…”
Section: Effector and Regulatory Immune Cells And The Renal Inflammatmentioning
confidence: 99%
“…We and others have demonstrated that CD14 + HLA-DR -/low cells share multiple characteristics with MDSCs [15] and expand under a variety of pathological conditions, such as cancer [16][17][18][19], inflammation [20,21], and autoimmune diseases [22,23]. Presently, the inhibitory properties of MDSCs are thought to be mediated by a number of different mechanisms, including arginase-1 (Arg-1), inducible nitric oxidase (iNOS), transforming growth factor-beta (TGF-β), and interleukin-10 (IL-10) as well as the induction of regulatory T cells [10,23].…”
Section: Introductionmentioning
confidence: 99%